Relationship Between Anti-Müllerian Hormone and In Vitro Fertilization-Embryo Transfer in Clinical Pregnancy - Sun, Xing Yu; Lan, Yun Zhu; Liu, Shuang; Long, Xiao Ping; Mao, Xi Guang; Liu, Ling (Frontiers in Endocrinology, 2020)
Objectives: To retrospectively analyze the correlation between AMH and the number of oocytes obtained by controlled ovarian hyperstimulation (COH) in women of different ages, and to explore the factors that affect the clinical pregnancy of infertile women in vitro fertilization and embryo transfer (IVF-ET), so as to provide evidence for infertile women to choose assisted reproduction strategies. Methods: Infertile women who received IVF-ET/ICSI-ET treatment in the reproductive center of our hospital between October 2018 and September 2019 were included. Mainly collect patient medical records, age, body mass index (BMI), years of infertility, basic follicle stimulating hormone (FSH), basic luteinizing hormone (LH), basic estradiol (E2), Anti-Mullerian hormone level (AMH), antral follicle count (AFC), gonadotropins (Gn) medication days, Gn dosage, endometrial thickness on transplantation day, number of retrieved oocytes, number of mature oocytes obtained, the number of embryos transferred and clinical pregnancy status, etc. Results: A total of 314 patients were enrolled in this study, with an average age of 31.0±4.5 years, and the infertility period ranged from 0 to 21 years. The AMH level shows a downward trend with increasing age; as a whole, the AMH level of women of all ages is positively correlated with the number of retrieved oocytes (r= 0.335, p<0.001); the AMH level of women between 22 and 28 years old. There was a positive correlation with the number of retrieved oocytes (r = 0.164, p<0.061), but it was not statistically significant; the AMH level of women aged 29 to 35 and 36-43 was also positively correlated with the number of retrieved oocytes (r = 0.356, p< 0.001; r = 0.461, p<0.001). The average age of the pregnant group (30.6±4.4 years) was lower than that of the non-pregnant group (32.2±4.6 years) (p<0.001). The number of oocytes obtained (9.8±4.5) and the number of embryo transfers (1.9±0.4) in the pregnant group were significantly higher than those in the non-pregnant group (9.2±4.5; 1.7±0.5), and the difference was statistically significant. The multivariate logistic regression model showed that age (OR=0.574 95% CI: 0.350-0.940), AMH (OR=1.430 95% CI: 1.130-1.820) and number of oocytes obtained (OR=1.360 95% CI: 1.030-1.790) are factors affecting clinical pregnancy.